(untitled) (e-Journal of Linguistics, 2020)
This research investigated the rhetorical moves in the introduction part to the research article written by graduate students in Linguistics master’s study programs. The primary purpose of this research is to describe the pattern of rhetorical moves in the research article introductions in the field of Linguistics. The data collection technique was in the form of scientific article documentation consisting of seven research article introductions in English in the field of Linguistics. Researchers collected data in the form of text with document analysis and note-taking techniques. These research articles were taken from four different journal publishers in Indonesia, namely Alphabet, Kelasa, Batra, and Suar Betang. The rhetorical analysis in this study involves the concept of the Project Justifying Model (PJM) proposed by Safnil (2010), which consists of four communicative moves that can describe the rhetorical moves of Indonesian writers. The validity of the data in this rhetorical pattern study used the triangulation of sources or data. The results of this study indicate that the seven introductions have different rhetorical moves. The four research article introductions taken from the Alphabet produced fewer rhetorical steps compared to the other three research articles. The most dominant signal found in the seven research article introductions is (move 4, step A) represents a statement in explaining the purpose of the study. The seven research article introductions found no statements that represented the five steps contained in each move.